All's well that ends well? A test of the peak‐end rule in couples' conflict discussions. (20th November 2018) - Sels, Laura; Ceulemans, Eva; Kuppens, Peter
Abstract: Despite its importance for well‐being, surprisingly little is known about what determines how couples feel after a conflict. Using the peak‐end rule, we examined whether partners' post‐conflict affect was mainly predicted by their most aversive or pleasant emotional experience (peaks) during the conflict, or by the emotional tone at the end of the interaction. One hundred and one couples engaged in a conflict interaction and afterwards evaluated their momentary affect during the interaction. Post‐conflict affect (in terms of positive and negative feelings, and perceived partner responsiveness) was assessed immediately after the conflict, after a subsequent positive discussion, and upon returning to daily life (here, rumination about the relationship was assessed as well). Our results showed that the negative and positive peaks, but not the end emotion, predicted immediate and partly extended post‐conflict affect in individuals. This finding has clinical implications for the mediation of couple conflict.